2021
DOI: 10.2196/24633
|View full text |Cite
|
Sign up to set email alerts
|

Digital Medical Device Companion (MyIUS) for New Users of Intrauterine Systems: App Development Study

Abstract: Background Women choosing a levonorgestrel-releasing intrauterine system may experience changes in their menstrual bleeding pattern during the first months following placement. Objective Although health care professionals (HCPs) can provide counseling, no method of providing individualized information on the expected bleeding pattern or continued support is currently available for women experiencing postplacement bleeding changes. We aim to develop a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We identified more papers providing a description. For example, Karakoyun et al [ 49 ] referred to the FDA definition of medical apps [ 42 ]. In contrast, Azad-Khaneghah et al [ 50 ] cited the definition of health apps by Morse et al [ 51 ], and Sun et al [ 52 ] used the description of health apps by Aitken and Lyle [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified more papers providing a description. For example, Karakoyun et al [ 49 ] referred to the FDA definition of medical apps [ 42 ]. In contrast, Azad-Khaneghah et al [ 50 ] cited the definition of health apps by Morse et al [ 51 ], and Sun et al [ 52 ] used the description of health apps by Aitken and Lyle [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review from 2018 showed that mobile health application usage has a positive impact on health-related behaviours and clinical health outcomes ( Han and Lee, 2018 ). Several studies have shown the benefits of specific health apps, such as an app aimed to improve self-care quality in heart failure ( Bakogiannis et al, 2021 ), an app to counsel women who use an intrauterine system ( Karakoyun et al, 2021 ), and an app to improve health outcomes of diabetics ( Ghose et al, 2022 ); however, there are fewer holistic web tools that offer a comprehensive preventive health approach. One such tool, the Wellness-Portal, is a novel web-based patient portal focused on wellness, prevention, and longitude health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of AI to power “software as a medical device” [ 15 ] presents an opportunity to leapfrog access to diagnostic devices, such as ultrasounds [ 16 ] and blood pressure equipment [ 17 ]. This has also been seen with the emergence of contraceptive and fertility software applications [ 18 , 19 ], which are increasingly securing regulatory approvals from national authorities [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%